Expression of SARS-CoV-2 receptor ACE2 and TMPRSS2 in human primary conjunctival and pterygium cell lines and in mouse cornea - Ma, Di (Eye (Lond), 2020)
PURPOSE: To determine the expressions of SARS-CoV-2 receptor angiotensin-converting enzyme 2 (ACE2) and type II transmembrane serine protease (TMPRSS2) genes in human and mouse ocular cells and comparison to other tissue cells. METHODS: Human conjunctiva and primary pterygium tissues were collected from pterygium patients who underwent surgery. The expression of ACE2 and TMPRSS2 genes was determined in human primary conjunctival and pterygium cells, human ocular and other tissue cell lines, mesenchymal stem cells as well as mouse ocular and other tissues by reverse transcription-polymerase chain reaction (RT-PCR) and SYBR green PCR. RESULTS: RT-PCR analysis showed consistent expression by 2 ACE2 gene primers in 2 out of 3 human conjunctival cells and pterygium cell lines. Expression by 2 TMPRSS2 gene primers could only be found in 1 out of 3 pterygium cell lines, but not in any conjunctival cells. Compared with the lung A549 cells, similar expression was noted in conjunctival and pterygium cells. In addition, mouse cornea had comparable expression of Tmprss2 gene and lower but prominent Ace2 gene expression compared with the lung tissue. CONCLUSION: Considering the necessity of both ACE2 and TMPRSS2 for SARS-CoV-2 infection, our results suggest that conjunctiva would be less likely to be infected by SARS-CoV-2, whereas pterygium possesses some possibility of SARS-CoV-2 infection. With high and consistent expression of Ace2 and Tmprss2 in cornea, cornea rather than conjunctiva has higher potential to be infected by SARS-CoV-2. Precaution is necessary to prevent possible SARS-CoV-2 infection through ocular surface in clinical practice.